Manajemen Kesehatan Reproduksi Remaja - Marliana Rahma; Achmad Sanusi; Fachruroji Fachruroji; Nandang Koswara (Jurnal Kebidanan Harapan Ibu Pekalongan, 2021)
The case of maternal mortality in Subang Regency is still high. One of the pockets of the problem lies in the youth group. Teenagers with anemia, teens with unwanted pregnancies, teens with early marriage, to free sex. The root cause of the emergence of these problems is the lack of knowledge of adolescents about reproductive health. The purpose of this study was to analyze the management of adolescent reproductive health in the students of SMP N 2 Subang. The method in this study uses a qualitative approach with descriptive methods through data analysis in the form of interviews, observations and document studies. Informants in this study were principals, vice principals for curriculum, biology subject teachers, and students of SMPN 2 Subang. The research location is SMP N 2 Subang. The results of the study show the following: (1) Planning has not been effective because it has not represented the school's vision based on a healthy environment (2) Organizing has been running effectively, there are responsibilities and organizational structures (3) Implementation has not been effective because there are limited media/teaching materials (4 ) Supervision has not been effective because there is no compliance control for consuming blood-added tablets (5) The evaluation is effective because it involves the principal, vice principal in curriculum, Biology subject teachers and students (6) The inhibiting factor lies in the lack of learning media, lack of education and lack of supervision.